Exploring Patient Trust Dimensions to Enhance Patient Satisfaction in Amarilis 2 Inpatient Ward at Dr. Adhyatma MPH Hospital Semarang - Setiawan, Lilik; Sukmawati, Nita (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Patient trust, medical expertise, and care experience play a crucial role in shaping effective and satisfying healthcare services within a hospital setting. This research explores the dimensions of patient trust, involving the security of personal information, trust in medical expertise, and confidence in the care experience, along with their impact on overall patient satisfaction. This study aims to address this research gap by meticulously examining patient trust dimensions and their effects on patient satisfaction in the Amarilis 2 inpatient ward. The study population consists of 72 patients in the Amarilis 2 ward at Dr. Adhyatma MPH Hospital in Semarang. The sampling technique employed a census approach, resulting in a sample size of 72 respondents. Data collection was conducted through a Google Form shared via a link for questionnaire completion. The research findings indicate that trust in the security of personal information, trust in medical expertise, and trust in the care experience have a positive and significant impact on patient satisfaction.